ANTI-BREAST CANCER POTENTIAL AND WATER SOLUBILITY OF ETHYL ACETATE LEAF EXTRACT TEA FROM Uncaria gambir Roxb: POTENSI ANTI-KANKER PAYUDARA DAN KELARUTAN AIR DARI EKSTRAK DAUN TEH ETIL ASETAT DARI Uncaria gambir Roxb - Virnalizi Dwimaharany; Dodi Iskandar; Desdy Hendra Gunawan (ROCE : Jurnal Pertanian Terapan, 2026)
The leaf extract of Uncaria gambir (UGR) was evaluated for its anticancer potential against 4T1 cells in vitro. Variations in soaking duration and mesh size affected extract yield, with 72-hour soaking and a mesh size of 60 producing the highest yield (32.6%). Polyphenolic compounds, particularly catechins, were identified as the main bioactive components, exhibiting dose-dependent cytotoxic effects, including induction of apoptosis, inhibition of cell proliferation, and modulation of oxidative stress. The IC₅₀ value of the UGR leaf water extract in this study was 1006.2 µg/mL, higher than previous reports (87.7 µg/mL), likely due to differences in extraction methods, solvent type, and analytical protocols. Water solubility data are relevant to pharmaceutical characterization, given the solubility and bioavailability challenges of catechins. These findings suggest that optimizing extraction methods or using catechin-rich fractions can enhance the anticancer potential of UGR. The study supports the potential of UGR as a breast cancer chemopreventive agent, highlighting the importance of appropriate extraction techniques to maximize bioactive compound content.